Family planning barriers and enablers among displaced Somali women in Ali Addeh Camp, Djibouti - Barkat, Ahmed Mohamed; Oladokun, Adesina; Adhana, Mache Tsadik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Sexual and reproductive health is essential to human rights, yet displaced populations, particularly women, face numerous barriers to accessing family planning services. This cross-sectional study aimed to explore the barriers and enablers of contraceptive use among Somali refugee women in the Ali Addeh Refugee Camp, Djibouti. Methods: A qualitative, exploratory design was used, incorporating focus group discussions (FGDs) with Somali refugee women. A total of 49 women participated, organized into seven groups based on marital status and age. Thematic analysis was conducted, focusing on barriers, enablers, and social dynamics related to family planning. Results: Major barriers cited were religious opposition, misinformation, and sociocultural resistance. Interestingly, 79.6% of the respondents desired large families, 67.3% of whom desired 18 to 35 months of birth spacing. While 40.8% of the women had 1-2 children, 34.7% of the women had five or more children. Contraception was viewed as foreign or religiously prohibited by most women, and 22 women cited religion. Male endorsement of family planning decisions was present, with 27 women reporting that spousal disapproval was a significant deterrent. Privacy concerns were common, with 18 women reporting stigma and fear of judgment among healthcare providers. Despite such barriers, trust in healthcare providers, religious endorsement, and community outreach were reported as facilitators of family planning. Conclusions: The study underscores the need for men and religious leaders' involvement in family planning. Interventions for displaced women should also prioritize privacy in health facilities, accessible and culturally acceptable family planning services.